The Effect of Image Media to Improve Essay Writing Descriptions Ability by Seventh Grade Students of SMP N 1 Paranginan in Academic Year 2018/2019.: The Effect of Image Media to Improve Essay Writing Descriptions Ability by Seventh Grade Students of SMP N 1 Paranginan in Academic Year 2018/2019. - Tanggapan C. Tampubolon (Institute of Computer Science (IOCS), 2020)
This study aims to determine the Effect of Image Media to Improve Essay Writing Descriptions Ability by Seventh Grade Students of SMP N 1 Paranginan with the total 175 students. The sampling uses a random sample technique, in class VII-A with a total of 30 students. The method use in this study is experimental method with one group pre-test and post-test design. The instrument is used Essay test. From the data processing the results of the pre-test were obtained with an average is 65, standard deviation = 6.94. Average post-test results = 77.66 and standard deviation = 8.17. From the test data the results of the pre-test and post-test obtained both results were normally distributed. Homogeneity test found that the sample of this study came from a homogeneous population. After the normality and homogeneity test, the value is 6.42 with ttable at a significant level of 5% with df = N-1 = 30-1 = 29 obtained a ttable value is 2.04. These results indicate the value of tcount is 6.42> 2.04, then the hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Then can be conclude that there is Effect of Image Media to Improve Essay Writing Descriptions Ability by Seventh Grade Students of SMP N 1 Paranginan in Academic Year 2018/2019.